Penerapan Strategi Pembelajaran Kontekstual Untuk Meningkatkan Hasil Belajar Pada Mata Pelajaran IPA Kelas V - Mikael Bumbun; Silvester Silvester (Jurnal Bintang Pendidikan Indonesia, 2024)
Learning that has so far been carried out only using conventional methods which are not in accordance with the characteristics of students. The results of the learning that has been carried out do not impress the children, therefore only the teacher is active in the class, the students are passive. So the science learning outcomes in class V at SDN 01 Bengkayang are low. This research aims to determine the science learning outcomes of fifth grade students SDN 01 Bengkayang Academic Year 2023/2024 before and after using contextual learning strategies. The type of research used in this research is classroom action research which consists of two cycles.This research uses a science learning outcomes test in the form of choices multiple materials on types of roots and their uses. The subject of this research is There are 20 fifth grade students at SDN 01 Bengkayang, consisting of 12 boys and 8 girls. The results obtained in this research were that there was an increase in science learning outcomes for class V students at SDN 01 Bengkayang. The increase in student learning outcomes was that in the pre-cycle 7 students (35%) had completed, in the first cycle there were 11 students (55%), while in the second cycle all students consisting of 20 students had fulfill the KKM or can be said to be complete (100%). This it can be concluded that the use of contextual learning strategies can improve the learning outcomes of class V students at SDN 01 Bengkayang through contextual learning strategies.